Efficacy and safety of isosorbide mononitrate plus misoprostol compared to misoprostol alone in the management of the first and second trimester abortion: a systematic review and meta-analysis - Somayeh Makvandi; Leila Karimi; Masoumeh Safyari; Mona Larki (BMC, 2024)
Abstract Background However, misoprostol is often used to terminate a pregnancy, but it can also cause side effects. Isosorbide mononitrate (ISMN) can help the cervix mature by increasing the production of prostaglandin E2 and vasodilation. Considering that the results of studies in this field are contradictory, it is the purpose of this study to evaluate the efficacy and safety of vaginal ISMN plus misoprostol compared to misoprostol alone in the management of first- and second-trimester abortions. Method The search process was conducted for MEDLINE through the PubMed interface, Scopus, Web-of-Science, Science Direct, the Cochrane Central Register of Controlled Trials (CENTRAL), Google Scholar, ClinicalTrials.gov, and the World Health Organization International Clinical Trials Registry Platform until November 10, 2023. Our assessment of bias was based on version 2 of the risk-of-bias tool (RoB2) for randomized trials and our level of evidence quality was determined by GRADE. Meta-analysis of all data was carried out using Review Manager (RevMan) version 5.1. Result Seven randomized clinical trials were included in the systematic review and three in the meta-analysis, with mixed quality. The results of the meta-analysis revealed that in the second-trimester abortion, the inclusion of ISMN in conjunction with vaginal misoprostol results in a noteworthy reduction in the induction abortion interval, specifically by 4.21 h (95% CI: -7.45 to -0.97, P = 0.01). The addition of vaginal ISMN to misoprostol, compared to vaginal misoprostol alone, increased the odds of a completed abortion by 3.76 times. (95% CI: 1.08 to 13.15, P = 0.04). Conclusion The findings of this study can offer valuable insights aimed at enhancing counseling and support for non-surgical methods of medication abortion within professional settings. Moreover, it improves the effectiveness of clinical treatment and reduces the occurrence of unnecessary surgical interventions in the abortion management protocol.